Sustainable Innovation in Everyday Wearable Bag Design: The Case of Oh My Craft! - Sylvia; Brylia Sheron Elbiqueen Tumanduk; Danantha Keithlin Halim; Monika Karnadi; Rayhan Pratama Putra (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Oh My Craft! is a micro, small, and medium enterprise that specializes in crafting bags made from traditional Indonesian textiles, marketed both online and offline. The company actively engages in sustainability by repurposing fabric and leather waste into other innovative products. This paper explores sustainable practices and innovation in traditional bag product design while focusing on voice of customers. From preliminary surveys to their customers, more than 50% of customers place significant importance on the functionality of bags—such as size, capacity, and features when making a purchase decision. The customers also suggested that Oh My Craft! introduce product variations based on bag functionality. The purpose of this paper is to recommend bag product design innovation that will fulfill sustainability practice and voice of customers with Quality Function Development method. The outcome is an innovative two-ways sling-tote batik bag product design with enhanced functionality that can be used both as small sling bag and shopping tote bag, designed to meet the needs of Oh My Craft!'s market, while minimizing material waste and promoting the reuse of materials.